US consumer attitudes toward sodium in baby and toddler foods. (1st August 2016) - John, Katherine A.; Cogswell, Mary E.; Zhao, Lixia; Maalouf, Joyce; Gunn, Janelle P.; Merritt, Robert K.
Abstract: Dietary data from a nationally representative survey indicate about 80% of US toddlers aged 1–3 years consume too much dietary sodium, which can influence their preference for salty foods in later life. Information on consumer attitudes can inform strategies to reduce sodium in baby and toddler foods. Data were obtained from a 2012 online survey sent to a sample of 11636 US adults aged ≥18 years enrolled in a national probability-based consumer panel; 6378 completed the survey and had non-missing responses to the question of interest, "It is important for baby and toddler foods to be low in sodium." Prevalence of agreement was estimated. Logistic regression was used to describe associations of respondent characteristics with agreement. The majority of respondents were non-Hispanic white and had a household income ≥$60, 000. About 7 in 10 (68%, 95% CI: 66%–70%) respondents agreed it is important for baby or toddler foods to be low in sodium. More than 6 of 10 respondents in most subgroups agreed. Among parents with a child currently aged <2 years (N = 390), 82% agreed (95% CI: 77%–87%); the highest agreement included parents who thought sodium was very harmful to their own health (92%, 95% CI: 85%–99%) or who were watching/reducing their own sodium intake (95%, 95% CI: 90%–100%). After adjusting for sex, age, race-ethnicity, agreement was most strongly associated with being a parent of a child <2 years, thinking sodium was harmful, and watching/reducing sodium intake (adjusted odds ratios ≥ 2.5, 95% CI's ≠1.0). The majority of respondents including most parents agreed it is important for baby and toddler foods to be low in sodium, suggesting wide consumer support for strategies to lower sodium in these foods.